FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN MANUFAKTUR SUBSEKTOR OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016: Factors Affecting the Value of Automotive Subsector Manufacturing Companies Listed On the Indonesia Stock Exchange for The 2012-2016 Period - Yanuar Dwi Syahbani; Martini (DRPM Universitas Budi Luhur, 2021)
This research aims to know the influence of profitability, liquidity, solvency, and firm size to firm value. The population for this research is the automotive manufacturing sub-sectors listed in Indonesia Stock Exchange in 2012-2016. Sample selection has been obtained by using purposive sampling method. The sample used was 9 companies. The analysis technique used for this research is using multiple regressions analysis. The research result shows profitability and size firm has effect on firm value, while liquidity and solvency has not effect on firm value